Selective Oxidation Using Flame Aerosol Synthesized Iron and Vanadium-Doped Nano-TiO2 - Zhong-Min Wang; Endalkachew Sahle-Demessie; Ashraf Aly Hassan (Journal of Nanotechnology)
Selective photocatalytic oxidation of 1-phenyl ethanol to acetophenone using titanium dioxide (TiO2) raw and doped with Fe or V, prepared by flame aerosol deposition method, was investigated. The effects of metal doping on crystal phase and morphology of the synthesized nanostructured TiO2 were analyzed using XRD, TEM, Raman spectroscopy, and BET nitrogen adsorbed surface area measurement. The increase in the concentration of V and Fe reduced the crystalline structure and the anatase-to-rutile ratios of the synthesized TiO2. Synthesized TiO2 became fine amorphous powder as the Fe and V concentrations were increased to 3 and 5%, respectively. Doping V and Fe to TiO2 synthesized by the flame aerosol increased photocatalytic activity by 6 folds and 2.5 folds, respectively, compared to that of pure TiO2. It was found that an optimal doping concentration for Fe and V were 0.5% and 3%, respectively. The type and concentration of the metal dopants and the method used to add the dopant to the TiO2 are critical parameters for enhancing the activity of the resulting photocatalyst. The effects of solvents on the photocatalytic reaction were also investigated by using both water and acetonitrile as the reaction medium.